Contributions of Red Lists of Ecosystems to risk-based design and management of protected and conserved areas in Africa - Keith, David; Ghoraba, Somaya; Kaly, Eric; Jones, Kendall; Oosthuizen, Ane; Obura, David; Daniels, Fahiema; Duarte, Eleutério; Grantham, Hedley; Gudka, Mishal; Norman, Juliet, Salome; Shannon, Lynne; et al. (My University, 2022)
Protected and Conserved Areas (PCAs) are key ecosystem management tools for conserving biodiversity and sustaining ecosystem services and social co-benefits. As countries converge on a 30% target for protection of land and sea under the post-2020 framework of the United Nations Convention on Biological Diversity, a critical question emerging is, “which 30%?”. One approach to an answer is risk-based: we should protect the 30% that returns the greatest reductions in risks of species extinction and ecosystem collapse. IUCN Red List protocols provide practical methods for assessing these risks. All species, including humans, depend on the integrity of ecosystems for their well-being and survival. Africa is strategically important for ecosystem management due to convergence of high ecosystem diversity, intense pressures and high levels of human dependency on nature. We reviewed the outcomes of a symposium at the inaugural African Protected Areas Congress convened to discuss applications of the IUCN Red List of Ecosystems to the design and management of PCAs. We found significant recent progress in red listing, with c. 1000 ecosystem types assessed across 21 countries. While these span a diversity of environments across the continent, the greatest thematic gaps are in freshwater, marine and subterranean realms and large geographic gaps exist in north Africa and parts of west and east Africa. The projects are implemented by a diverse community of government agencies, NGOs and researchers. Already, they are having impact on policy and management, informing extensions to formal Protected Area networks, supporting decision making for sustainable development and informing ecosystem conservation and threat abatement, both within boundaries of PCAs and in surrounding landscapes and seascapes. We recommend further integration of risk assessments into environmental policy and enhanced investment in ecosystem red listing to fill current gaps.
Supplemental Materials: https://osf.io/p5n9q/
Keywords: Ecosystem management; Endangered ecosystems; Key Biodiversity Areas; Protected Areas; Red List of Ecosystems; Risk reduction